Impact of Regulation on the Physico-chemical Features and Zooplanktonic Diversity of Central Himalayan River Tawi in Udhampur (J&K) INDIA - Mohan, Vikas Chander; Sharma, K.K.; Sharma, Arti (International Multidisciplinary Research Journal, 2014)
Flow of rivers become impeded and are regulated due to construction of dam. This brings about change in abiotic and biotic factors compared to unregulated river. The post-impoundment physical, chemical and biological parameters of the parent river Tawi (upstream, within reservoir and downstream) were analysed for the first time and data thus generated was compared to reveal influence of dam on this regulated river. It was observed that the water temperature, pH, transparency and carbon dioxide content of the parent river were influenced by the dam and significant differences in these parameters were observed among the main zones sampled. The zooplanktonic community of river Tawi was also influenced by variations in abiotic features and its highest planktonic diversity was recorded in reservoir (lentic zone) of dam due to reduced water current, higher transparency and long resident time where as downstream river exhibited low diversity due to lotic conditions.